Gut microbiota and their metabolites ameliorate acute and chronic colitis in mice via modulating Th17/Treg balance - Li, Dongyue; Tao, Huiling; Tan, Xin; Ling, Hao; Lu, Yue; Zhang, Huichao; Theany, Sok; Xu, Hongyu (Frontiers in Microbiology, 2025)
IntroductionUlcerative colitis (UC) is a recurrent inflammatory bowel disease affecting the colorectum, which remains a prominent research focus due to significant individual variations in clinical therapeutic outcomes. Fecal microbiota transplantation (FMT), as a therapeutic approach to restore intestinal homeostasis, has demonstrated favorable efficacy in UC management. However, given the characteristic alternating cycles of active and remission phases in UC, there remains a paucity of in-depth research regarding the optimal timing for FMT intervention. Concurrently, butyrate - a crucial microbial metabolite - ameliorates murine colitis through both direct and indirect mechanisms, while the therapeutic effectiveness of FMT in UC correlates closely with intestinal butyrate concentration.MethodsThis study established acute and chronic UC murine models and employed FMT and butyrate interventions to monitor dynamic alterations in gut microbiota and lymphocyte subsets. Through comprehensive analyses, we aimed to elucidate the interplay between gut microbiota and host immune mechanisms, identify the optimal therapeutic timing for UC interventions, and evaluate the mechanistic role of butyrate. These findings provide theoretical foundations for personalized microbiota-targeted therapies in UC.ResultsOur findings demonstrate that gut microbiota and their metabolites exert therapeutic effects on murine acute/chronic colitis through modulation of the T helper cell 17 (Th17)/T regulatory cell (Treg) ratio. Specifically, the remission phase represents a more favorable window for intestinal homeostasis modulation, with combination therapy involving microbial metabolites exhibiting superior anti-inflammatory efficacy.DiscussionThe maintenance of an appropriate Th17/Treg equilibrium during microbiota restoration demonstrates therapeutic advantages. Notably, butyrate synergistically enhances microbial therapeutic effects, providing experimental evidence for personalized modulation of gut ecosystems in inflammatory bowel disease management.